Analisis Kinerja Keuangan Retribusi Pelayanan Parkir di Tepi Jalan Umum pada Pemerintah Kabupaten Sumedang Tahun Anggaran 2018-2022 - Tanisya Aulia Fadilla; Ivan Yudianto (Universitas 45 Surabaya, 2024)
Local Own-Source Revenue (PAD) is vital in the government's implementation in meeting its needs and services to society. One of the components of PAD is Local Retribution. Sumedang Regency has various local retributions, which various authorized agencies manage, and one of them is the parking retribution on the side of the public road. This research aims to determine and describe the financial performance of parking retribution on the side of the public road. This research uses descriptive research methods, with data collection techniques through documentation studies and interviews. The research results show that the average effectiveness ratio of parking retribution on the side of the public road in 2018-2022 is 64.23%, classified as ineffective. Meanwhile, the contribution made to PAD is only 0.17%, which is categorized as very low. However, the analysis of income growth from retribution is dominated by positive growth. In 2021 and 2022, revenue growth could reach 650% and 66%. There is a positive impact from the implementation of subscription parking.